The ewe as an animal model of vaginal atrophy and vaginal Er: YAG laser application. Issue 2 (February 2021) - Hympanova, Lucie; Rynkevic, Rita; Mori Da Cunha, Marina G. M. C.; Diedrich, Chantal M.; Blacher, Silvia; De Landsheere, Laurent; Mackova, Katerina; Krofta, Ladislav; Roovers, Jan-Paul; Deprest, Jan
Abstract: Objective: In sheep of reproductive age, we aimed to document decrease in epithelial thickness, glycogen amount, and other vaginal changes after castration and the effect of Er:YAG laser as used clinically. Methods: On day 0, 16 sheep underwent ovariectomy. They were randomized to sham or three vaginal Er:YAG laser applications at monthly intervals. Primary outcome was vaginal epithelial thickness (d60, d71, d73, d77, and d160). Secondary outcomes included indicators of atrophy (vaginal health index = VHI), pH, cytology, morphology at the above time points, microcirculation focal depth (FD; d70 and d160), and at sacrifice (d160) vaginal dimensions and active and passive biomechanical testing. Results: Menopausal changes between 60 and 160 days after ovariectomy included a progressive decrease in epithelial thickness, in VHI, FD, glycogen, elastin content and vasculature, and an increase in pH and collagen content. In lasered animals, the first day a few white macroscopic foci were visible and an increase in pH was measured. Both disappeared within 3 days. Seven days after laser the epithelial thickness increased. At sacrifice (d160), there were no differences between sham and laser group in vaginal dimensions, morphometry, mitotic and apoptotic activity, active contractility, vaginal compliance, except for a lower blood vessel density in the lamina propria of the midvagina in the laser group. Conclusions: In reproductive sheep, ovariectomy induces vaginal atrophy evidenced in different outcome measurements. Vaginal Er:YAG laser induced visual impact, a short-term increase in epithelial thickness yet no long-term changes compared to sham therapy in menopausal controls. N/A: Video Summary: http://links.lww.com/MENO/A672 . Abstract : Supplemental Digital Content is available in the text